Comparative toxicity study on classical and modified version of Jawarish Jalinoos (a traditional Unani formulation) in rats - Gulam Mohammed Husain; Syed Shoeb Ahmed; Misbahuddin Azhar; Javed Inam Siddiqui; Mohammad Abdul Waheed; Munawwar Husain Kazmi (Integrative Medicine Research)
Background: Jawarish Jalinoos (JJ) is a classical semisolid traditional Unani formulation clinically used for the treatment of weakness of vital organs, liver, and stomach. Although JJ has been widely used clinically for several decades, no scientific report is available for its safety. Methods: JJ and its sugar-free tablet version (SFJJ; formulated to target diabetic population) were assessed for safety in rats. Ninety-day repeated dose oral toxicity study was performed as per the Organisation for Economic Co-operation and Development Guideline 408. JJ was orally administered at the dose of 2000 mg/kg bw/d, whereas SFJJ was orally administered at the doses of 506 mg/kg body weight (bw)/d, 1012 mg/kg bw/d, and 2024 mg/kg bw/d for 90 days. The animals were periodically observed for clinical signs of toxicity, mortality, morbidity, body weight changes, and feed consumption. At the end of the study, hematology, clinical biochemistry, electrolytes, gross pathology, relative organ weight, and histological examination were performed. Results: Treatment with SFJJ and JJ showed no significant differences in body weight gain, feed consumption, hematology, clinical biochemistry, and serum electrolytes. No gross pathological findings and differences in relative organ weights were observed between control and drug treated rats. Histological examination revealed no toxicologically significant abnormalities related with SFJJ or JJ treatment. Conclusion: The 90-day repeated dose oral toxicity study demonstrates that the no observed adverse effect level of SFJJ and JJ is greater than 2024 mg/kg bw/d and 2000 mg/kg bw/d (p.o.) in rats, respectively. Both formulations were found to be safe up to the tested dose levels and experimental conditions, and therefore safe for clinical use as specified in the literature.